Effect of Helicobacter pylori Eradication on Epigenetic Changes in Gastric Cancer-related Genes - Ji Min Choi; Sang Gyun Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2021)
It is known that gastric carcinogenesis results from the progressive changes from chronic gastritis to gastric atrophy, intestinal metaplasia, dysplasia, and invasive carcinoma. Several genetic and epigenetic alterations are involved in this process, and Helicobacter pylori (H. pylori) infection is believed to induce the initiation and progression of these steps. From an epigenetic point of view, H. pylori induces hypermethylation of genes involved in the development of gastric cancer and regulates the expression of various microRNAs (miRNAs). These H. pylori-related epigenetic changes are accumulated not only at the site of neoplasm but also in the adjacent non-cancerous gastric mucosa. Thereby, a state vulnerable to gastric cancer known as an epigenetic field defect is formed. H. pylori eradication can have an effective chemopreventive effect in gastric carcinogenesis. However, the molecular biological changes that occur in the stomach environment during H. pylori eradication have not yet been established. Several studies have reported that H. pylori eradication can restore infection-related changes, especially epigenetic alterations in gastric cancer-related genes, but some studies have shown otherwise. Simply put, it appears that the recovery of methylated gastric cancer-related genes and miRNAs during H. pylori eradication may vary among genes and may also differ depending on the histological subtype of the gastric mucosa. In this review, we will discuss the potential mechanism of gastric cancer prevention by H. pylori eradication, mainly from an epigenetic perspective.